Branding Image of Zero Food Waste Management Actions for Corporate Reputation Development - Fazil Ahmad, Muhamad; Firdaus Muhammad Nurul Azmi, Aida; Abd Razak, Shukor (International Journal of Engineering and Technology, 2018)
Food waste is a global issue with environmental, social, and economic consequences. The problem with food waste has become more and more evident during recent years and a reduction of the waste would be one important step towards a more sustainable society. Food waste is a global issue with environmental, social, and economic consequences. As fast food industry strives to develop distinctive identities, deeper understanding about topics such as brand identity, meaning, image, and reputation will enable brand owners to communicate more effectively with stakeholders including shareholders, customers, employers, and others. Many studies have focused on investigating the sources of food waste from households, while very little is known about other outlets such as food plants and restaurants whose services contribute to the food waste amounts. The study was conducted through a literature review and interviews with the actors that included 3 QSR fast food restaurants management and 1 official from AYAMAS Food Corporation Sdn. Bhd. To broaden the scope of the research several supporting frameworks were utilized and aided in the generation of a complete understanding of the thoughts of the actors. The results from the research showed a variety of the actions they have taken to address the issue, and the opportunities and obstacles they see for the management of food waste. However, the environmental, economic, and social dimensions of the issue were acknowledged by the interviewees, being the latter the most relevant one for them, stating the importance of a change in behavior and raising of awareness and consciousness from all people towards the issue.Â Â